Prognosis and quality of life in patients with locally advanced rectal cancer after abdominoperineal resection in the CAO/ARO/AIO-04 randomized phase 3 trial - Gaedcke, Jochen Werner Christian; Sahrhage, Malte; Ebeling, Marcel; Azizian, Azadeh; Rühlmann, Felix; Bernhardt-Römermann, Markus; Grade, Marian; Beschstein, Wolf Otto; Germer, Christoph-Thomas; Grützmann, Robert; Piso, Pompiliu Ioan; Hofheinz, Ralf-Dieter; et al. (Scientific reports, 2025)
Low anterior resection (LAR) and abdominoperineal resection (APR) are the two main surgical procedures after preoperative chemoradiotherapy (CRT) for locally advanced rectal cancer. APR is associated with poorer prognosis; however existing data do not consider intensified CRT (5-Fluorouracil (5-FU)/Oxaliplatin + radiation) protocols. Clinicopathological data of patients treated with APR and LAR from the CAO/ARO/AIO-04 trial were analysed in terms of prognostic parameters and quality of life (QoL). Based on higher response rate after intensified CRT, subgroup analyses were performed. Data from n = 1173 patients were assessed. APR after preoperative CRT was associated with a significantly worse overall survival (p = 0.0056), disease-free survival (p < 0.0001) and local recurrence rate (p = 0.0047). Clinicopathological data including clinical T stage (p < 0.000001), grading (p = 0.0038), postoperative lymph node (LN) positivity (p = 0.013), and number of positive LN (p = 0.0049) significantly differed between procedures and showed higher values in APR patients. The quality of total mesorectal excision (TME) was significantly better (p < 0.0001) and complete resection rates were higher (p = 0.0022) in LAR compared to APR patients. Subgroup analyses showed worse LR rates in APR patients after standard CRT (5-FU mono and radiation) but not after intensified CRT. After 3 years, role functioning (p = 0.019) and physical functioning (p = 0.001) had a slightly poorer outcome in APR patients. The poorer prognosis of patients undergoing APR for locally advanced rectal cancer may be explained by clinicopathological characteristics. Intensified CRT may compensate for the higher risk of LR after APR in patients with worse TME quality. QoL in APR patients was comparable to LAR patients.
Gesehen am 10.07.2025